2011
DOI: 10.1128/cvi.05071-11
|View full text |Cite
|
Sign up to set email alerts
|

Single and Combination Herpes Simplex Virus Type 2 Glycoprotein Vaccines Adjuvanted with CpG Oligodeoxynucleotides or Monophosphoryl Lipid A Exhibit Differential Immunity That Is Not Correlated to Protection in Animal Models

Abstract: Despite several attempts to develop an effective prophylactic vaccine for HSV-2, all have failed to show efficacy in the clinic. The most recent of these failures was the GlaxoSmithKline (GSK) subunit vaccine based on the glycoprotein gD with the adjuvant monophosphoryl lipid A (MPL). In a phase 3 clinical trial, this vaccine failed to protect from HSV-2 disease, even though good neutralizing antibody responses were elicited. We aimed to develop a superior, novel HSV-2 vaccine containing either gD or gB alone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 33 publications
1
22
0
1
Order By: Relevance
“…The trivalent vaccine group outperformed gD2 alone despite inducing lower neutralizing antibody titers with and without complement, suggesting that neutralizing antibody titers are not sufficient to explain the vaccine protection [40]. It is possible that antibody-dependent cellular cytotoxicity contributed significantly to vaccine protection as reported for HSV-2 ΔgD2, a gD2 null live virus vaccine [41, 42].…”
Section: Discussionmentioning
confidence: 99%
“…The trivalent vaccine group outperformed gD2 alone despite inducing lower neutralizing antibody titers with and without complement, suggesting that neutralizing antibody titers are not sufficient to explain the vaccine protection [40]. It is possible that antibody-dependent cellular cytotoxicity contributed significantly to vaccine protection as reported for HSV-2 ΔgD2, a gD2 null live virus vaccine [41, 42].…”
Section: Discussionmentioning
confidence: 99%
“…Do these immune responses inhibit or exacerbate HSK? Data from experimental models suggest that these questions remain incompletely understood [82,86]. …”
Section: Animal Models and Ocular Hsv-1 Vaccinesmentioning
confidence: 99%
“…Likewise, natural killer cell recruitment and activation is in part dependent on interferon signaling. Augmentation of immune responses to HSV has been achieved in murine models with co-administration of the TLR9 agonist cPG [64]. Adjuvant development focused on maximizing stimulation of innate immunity may have a large impact on future candidate HSV vaccines [65,66].…”
Section: Innate and Adaptive Immunity To Hsvmentioning
confidence: 99%
“…Studies using lectin-purified gD and gB subunit vaccine demonstrated similar protection, not only against primary infection, but recurrent disease [79]. Adjuvant choice plays a crucial role in protection in adjuvanted glycoprotein studies in the guinea pig model, with adjuvants capable of eliciting robust cellular immune responses in additional to antibody responses appearing to enhance protection against disease [64,80-86]. Other novel routes of delivery of adjuvanted HSV glycoproteins have been evaluated, including intranasal administration [87,88].…”
Section: Lessons From Animal Models Of Hsv Vaccinesmentioning
confidence: 99%